Laserpuncture Shooting Duration Effect at the Growth Point on the Weight Gain and Growth Rate of Male Japanese quail (Coturnix coturnix japonica) - Aida Zharah; Yeni Dhamayanti; Sunaryo Hadi Warsito; R Tatang Santanu Adikara; Gracia Angelina Hendarti; Sri Hidanah (Universitas Airlangga, 2024)
Aim of this research is to find the effect of laserpuncture shooting at growth points on body weight gain and growth rate of male Japanese quail. This research used 20 samples Japanese male Day Old Quail (DOQ) with complete randomized design research method. These samples were divided into four groups. Group P0 (control) was treated by laserpuncture everyday with power supply off for 5 seconds. Group P1 was treated by laserpuncture every day with power supply at 50 mWatt and the dose was 0.2 Joule for 5 seconds. Group P2 was treated by laserpuncture every three days with power supply at 50 mWatt and the dose was 0.2 Joule for 5 seconds. Group P3 was treated by laserpuncture every five days with power supply at 50 mWatt and the dose was 0.2 Joule for 5 seconds. The samples was reared until 42 days. The result of the research were obtained from weighing the body weight every week and then substracting the results from the previous week. The data was analyzed statictically using the Multivariate Analysis of Variance (Manova) and continued with Duncan test. Group P3 showed the best results compared to other groups.